The lusophone world of Iberoamerica: between the “left wave” and the “right turn” (the example of Portugal and Brazil) - M. I. Sigachev; Yu. A. Timofeeva (Ибероамериканские тетради)
The authors analyze political cycles of the Portuguese (Lusophone) world, which is based on Portugal-Brazil civilizational axis. The authors seek to prove the existence of synchronicity and parallelism in the context of the movement of political pendulum from right to left and back within the Lusophone world of Iberoamerica. The main thesis of this study is that the Ibero-American transcontinental macro-region is sandwiched between a “left wave” and a “right turn”, with the conclusion that further continuation of the “left wave” with right-wing fluctuations in the current context is going to continue. As far as Portugal is concerned, the case of the municipal elections of September 26, 2021 is used as empirical material and is subjected to a detailed analysis from the perspective of the Portuguese party-political landscape. In addition, some attention is paid to the early parliamentary elections of January 30, 2022 in Portugal. The authors also assess the development of populism in Portugal, given that in European countries, left-wing and right-wing populist movements are gaining popularity. Similarly, the authors consider the results of the 2020 municipal elections, and political situation in Brazil on the eve of the 2022 presidential elections. We give a forecast about further shift to the left of the Ibero-American Lusophone world, if after the confident victory of the Portuguese socialists under the leadership of Costa the socialist president Lula da Silva comes to power in Brazil, and, as a result, about formation of the left-socialist power pole within the framework of the Ibero-American Lusophony.